Antiviral Efficacy of Abacavir in Antiretroviral Therapy-Experienced Adults Harbouring HIV-1 with Specific Patterns of Resistance to Nucleoside Reverse Transcriptase Inhibitors - Lanier, E Randall; Ait-Khaled, Mounir; Scott, Janna; Stone, Chris; Melby, Thomas; Sturge, Glenn; Clair, Marty St; Steel, Helen; Hetherington, Seth; Pearce, Gillian; Spreen, William; Lafon, Stephen (Antiviral therapy, 2004)
To evaluate HIV-1 reverse transcriptase genotypic and phenotypic indicators of resistance to abacavir (ABC) as predictors of ABC antiviral efficacy. The study was a retrospective, combined analysis of five multicentre trials in which ABC was added as a single agent to background antiretroviral therapy in experienced adults. Baseline HIV-1 genotype and phenotypic susceptibility to ABC were determined and the association of genotype and phenotype with virological response after addition of ABC was analysed. Overall, 68% of these therapy-experienced subjects had a virological response (>0.5 log10 or <400 copies/ml; 42% <400 copies/ml) 4 weeks after addition of ABC. Multivariable analyses revealed no significant difference in the response rate between subjects with wild-type virus and those carrying virus with 1-2 nucleoside reverse transcriptase inhibitor (NRTI)-associated mutations. At the 4-week time-point subjects harbouring virus with > or = 3 mutations associated with NRTI resistance were significantly less likely to respond to ABC than were subjects harbouring wild-type virus (P=0.015). However, at the last viral RNA measurement after addition of ABC (12-28 weeks), > or = 4 mutations were required to diminish virological response significantly (P=0.012). Phenotypic resistance was also predictive of antiviral response. Significant breakpoints were identified for virological responses for the PhenoSense HIV assay and the Antivirogram assay. CD4 responses generally paralleled the antiviral responses with a median increase of 55 cells/microl by weeks 12-28. Virological response to ABC may be diminished significantly by multiple NRTI-associated mutations and/or by reductions in phenotypic susceptibility to ABC. However, many subjects with baseline samples showing evidence of resistance to NRTIs respond to ABC.